Managing and Supervising Privatization of Islamic Education within a Decentralized Educational System in West Sumatra - Ika Sandra; Tiok Wijanarko; Nguyen Thi Hong Hanh; Evelynd Evelynd (Journal of Civic Education, 2023)
This article examines the management and supervision of Islamic education in West Sumatra within a highly decentralized educational system. It addresses the belief among Indonesians that centralized governance leads to regional unfairness and hinders community involvement. In a decentralized system, local governments have the autonomy to control their own functions, including education, aligning with the goals and needs of their communities. The growth of Islamic education in West Sumatra is a result of this decentralized system. This article using qualitative research methods such as document analysis and interviews and conducted in Padang and Padang Panjang as representative of Muslim regions in West Sumatra. Findings indicate that the planning process is initiated by the mayor, who appoints government institutions like Social Welfare Unit and Education Departments to oversee Islamic education in the region, following a top-down approach.